O'Connell, Kevin. Interview about his work in Newfoundland and Labrador Radio. - Swain, Hector K. (1990)
Kevin O'Connell talks about his work with CBC in radio broadcasting, and the early radio in Newfoundland and Labrador. 00:00 - Recording starts with part of a recorded prayer; 00:23 - Interview starts; Kevin O'Connell talks about starting in radio in 1948 in Corner Brook; Talks about different stations, CBC, Broadcasting Corporation of Newfoundland, VONF, VONH, VORG, and VOWM; 04:10 - The philosophy of the CBC; 06:50 - Talks about early radio stations in St. John's, small radio, VOWR; Radio in Gander, Corner Brook, Fort Pepperrall; 10:17 - Compare Newfoundland and Canadian Radio; 12:20 - Talk about religious programs; Morning Devotion; Sacred Heart program; Hymn programs; Lidstone sisters; 17:00 - Humanitarian programing and the Gerald S. Doyle Bulletin; 22:13 - Talks about The Woodland Echo, that was for men in lumber camps; 24:48 - Talks about the Sanatorium program in Corner Brook; 26:17 - O'Connell talks about Ted Russell and the Uncle Mose program; 29:58 - Joey Smallwood and The Barrelman; 31:50 - The Yarns of Sandy Joe; 32:42 - The Newfoundland Savings program that was very popular during the war; Margot Davies; 35:40 - Talks about Aubrey "Mac" MacDonald; 38:05 - Talks about school broadcasts; 39:58 - Talks about a St. Bon's operetta broadcast; Christian Brothers involvement in radio; 41:31 - Noel Murphy; Lester Burry.